Body composition and muscle strength predictors of jumping performance: Differences between elite female volleyball competitors and nontrained individuals - Copic, N.; Dopsaj, M.; Ivanovic, J.; Nešic, G.; Jaric, S. (The Journal of Strength and Conditioning Research, 2014)
Studies of the role of various anthropometric, physiological, and biomechanical variables in performance of rapid movements have generally revealed inconsistent findings. Within this study, we tested the hypotheses that (a) both body composition and leg extensor strength variables would reveal significant relationship with jumping performance, whereas (b) the same relationships would be stronger in physically active nonathletes than in the elite athletes proficient in vertical jumping. Top-level female volleyball players (VP; N = 35) and physically active female nonathletes (PA; N = 21) were tested on maximum vertical jumps performed with and without arm swing, as well as on body composition (percent fat and muscle) and leg press strength (maximum force and the rate of force development). The results revealed significant relationships between the jumping performance and body composition variables that appeared to be higher in PA (r = 0.65-0.76; all p < 0.01) than in VP (r = 0.37-0.42; all p < 0.05). The relationships between the jumping performance and the leg strength variables were mainly significant (r = 0.23-0.68) and similar in 2 groups. We conclude that not only the leg extensor strength but also the body composition variables could be valid predictors of jumping performance and, possibly, other rapid movements. Moreover, the body composition variables that have been mainly neglected in the literature could be particularly strong predictors of performance of jumping in nonathletes, as compared with relatively homogeneous populations of elite athletes.